(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Improvement of meat quality plays important role for sheep meat producer and costumer market. Leptin Receptor (LEPR) gene is speculated has important role in carcass and meat quality. This study aims to investigate the relationship between the LEPR gene variation with characteristics of carcass and meat quality in sheep. A total 50 rams consisted 20 of Javanese fat tailed (JFT), 10 of garut composite (GCS), 10 of compass agrinak (CAS), and 10 of barbados cross (BCS) were used in this study. Polymorphism of LEPR gene were performed by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) with Acil as restriction enzyme. The results showed that of the amplification product was 432 bp. The result of polymorphism of LEPR gene were polymorphic with third genotype including AA, AC, dan CC. The SNP of LEPR gene with genotype AA was associated (P<0.05) with carcass characteristics including empty body weight, cold carcass and with genotype AC on meat quality including tenderness. It could be concluded that the SNP g.40854778 A>C of LEPR gene may contribute to the characterictic carcass and meat quality in sheep